Underground Blast Monitoring and Rock Mass Anisotropy - Kelly Fleetwood; Ernesto Villaescusa; Ronald Lachenicht; Jody Todd (International Society of Explosives Engineers, 2008)
In the underground environment, characterisation of a rock mass during the mining cycle becomes increasingly difficult due to a lack of rock mass exposure for measurement or observation. In most cases rock mass characterisation occurs prior to mining by inspection and logging of exploration drill core, or prior to mass excavation through drive mapping for geological and geotechnical data. Characterisation strategies, if applied during the mining cycle, can reveal near-field anisotropies that may affect the behaviour of the rock mass with respect to excavation. These methods can aid in understanding the performance of stopes based on geometry, in-stope extraction sequence, and stress modelling. One such method of characterisation involves the use of production blast vibration monitoring and analysis as indicators of rock mass anisotropy through travel-time tomography.